Electron Spin Resonance Spin Probe Technique for Investigating Non-TEMPO Radicals Dispersed in Nanospaces of a Crystalline Zn Complex - Hirokazu Kobayashi; Kento Akiniwa; Fumiyasu Iwahori; Hidehiko Honda; Masato Yamamoto (Concepts in Magnetic Resonance: Part A, Bridging Education and Research)
An ESR spin probe technique with non-TEMPO radicals, such as nitronyl nitroxide (NN), benzonitronyl nitroxide (BzNN), and iminonitroxide (IN) radicals, was used for a porous metal-organic framework (MOF), [(ZnI2)3(TPT)2] (ZnTPT; TPT = tris(4-pyridyl)-1,3,5-triazine), at room temperature. The principal values of g and hyperfine coupling (A) tensors estimated from spectral reproduction were different from those for organic matrices for some of these radicals. These results indicate that host-guest interactions occur between the ZnTPT matrix and guest radicals. Thus, when using NN, BzNN, and IN radicals as spin probes for a porous MOF, the interaction between the metal atoms or organic ligands in host materials and guest radicals should be considered. The experimental ESR spectra for the derivatives of NN or BzNN radicals were reproduced only by the rigid-limit component in the ESR time scale. However, those for the derivatives of IN radicals were approximately reproduced only by rotational diffusion around the z-axis perpendicular to the plane in the IN group. Interestingly, this reproduction was not around the y-axis of the principal axes of the g tensors, parallel to the molecular long axis, as previously observed in a few organic matrices. The IN radicals dispersed in the ZnTPT matrix are expected to be accommodated in cylindrical or pseudocylindrical nanospaces sandwiched by the pyridyl or triazine rings of TPT in ZnTPT. These findings show that the ESR spin probe technique using non-TEMPO radicals can be used to investigate the chemical and biological structures of nanosized materials.